PENGARUH LINGKUNGAN KELUARGA DAN LINGKUNGAN PERGAULAN TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS XI IPS SMA NEGERI 3 KOTA JAMBI TAHUN 2012/2013 - Suratno, Suratno (Program Magister Teknologi Pendidikan Universitas Jambi, 2014)
This study aims to prove the allegations of the influence of family environment and social environment on student achievement on economic subjects, students of class XI IPS SMA N 3 Jambi City year 2012-2013. The results showed that the family environment and social environment jointly significant effect on their learning outcomes. Family environment is more dominant effect on student learning outcomes than their milieu. Keyword: Family Environment, Social Environment,Student Learning